2015
DOI: 10.1002/chem.201501598
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Synthesis of a Glycopeptide Derived from Skp1 for Probing Protein Specific Glycosylation

Abstract: Skp1 is a cytoplasmic and nuclear protein, best known as an adaptor of the SCF family of E3-ubiquitin ligases that label proteins for their degradation. Skp1 in Dictyostelium is posttranslationally modified on a specific hydroxyproline (Hyp) residue by a pentasaccharide, which consists of a Fucα1,2-Galβ-1,3-GlcNAcα core, decorated with two α-linked Gal residues. A glycopeptide derived form Skp1 was prepared to characterize the α-galactosyltransferase (AgtA) that mediates the addition of the α-Gal moieties, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…shifts were also compared with those of authentic chemically synthesized Fuc␣1-2Gal␤1-3GlcNAc␣1-4Hyp (27) and are in agreement. They are also in agreement with those of the CASPER database of all Fuc-Gal regioisomers (28) (supplemental Table S3).…”
Section: Glycan-induced Conformation Changementioning
confidence: 56%
See 2 more Smart Citations
“…shifts were also compared with those of authentic chemically synthesized Fuc␣1-2Gal␤1-3GlcNAc␣1-4Hyp (27) and are in agreement. They are also in agreement with those of the CASPER database of all Fuc-Gal regioisomers (28) (supplemental Table S3).…”
Section: Glycan-induced Conformation Changementioning
confidence: 56%
“…Previous studies suggested that the pentasaccharide consists of Gal␣1,3Fuc␣1,2Gal␤1,3GlcNAc␣1linked to 2S,4R-hydroxyproline, modified by an ␣Gal at an unknown position. However, these linkages were assigned based on indirect evidence, such as exoglycosidase sensitivity and in vitro characterization of the glycosyltransferase substrate preferences and product characterizations (12,(23)(24)(25)(26)(27). The NMR-based data presented here confirm the Fuc␣1,2Gal-and the Gal␣1,3Fuc linkages in the isolated glycopeptide, based on HMBC analysis and chemical shift comparisons with an authentic standard ( Fig.…”
Section: The Skp1 Glycan Sequencementioning
confidence: 58%
See 1 more Smart Citation
“…The reaction consisted of 6.25 M Toxoplasma Gn-Skp1, 112 nM Dictyostelium FLAG-PgtA, 25 M UDP-Gal, 50 M GDP-Fuc, 120 mM NaCl in 50 mM Tris-HCl (pH 7.5). The reaction was monitored by dot blotting onto nitrocellulose filters and probing with mAb 1C9, which is specific for Dictyostelium Gn-Skp1 relative to other modified glycoforms (15), and a 1:1000 dilution of polyclonal antibody UOK104, which is specific for Dictyostelium FGGn-Skp1 relative to other glycoforms (26). Alexa680-coupled secondary antibodies were applied and detected in an Odyssey infrared scanner (LI-COR).…”
Section: Preparation Of Toxoplasma Fggn-skp1mentioning
confidence: 99%
“…One reason for the limited acceptance of IgG glycoform quantification in clinical samples is the dominant production of less specific glycan fragments (oxonium ions) under CID conditions used typically for the fragmentation of glycopeptides 2830 . Another reason is the lack of synthetic isotope labeled standards (SIS) of glycopeptides which present a substantial synthetic challenge despite recent advances in the chemical and chemoenzymatic synthetic approaches 3134 . In the course of our study, Li and coworkers have reported a chemoenzymatic synthesis of an array of fucose isotope-labeled Fc glycopeptides for their absolute quantitation but the method is limited to core-fucosylated glycopeptides 35 .…”
Section: Introductionmentioning
confidence: 99%